Protection of Community Economic Rights in Mining Areas in North Sulawesi - Cacelia Waha (AIBPM Publisher, 2018)
Economic inequality of people in the mining area because mining investment activities are not beneficial in improving the welfare of the community. This is a serious problem that causes the occurrence of resistance and mining investment conflicts between investors and the surrounding community. The resistance was caused because the community was not involved in contracts made by mining companies with the local government. The community is always suspicious of contracts made related to mining exploration by foreign parties. The economic rights of the people in the mining area are not contradictory to the principles in Article 33 of the Constitution of 1945. The purpose of this study is to find a model for regulating the economic rights of communities in the mining area and a model of resistance prevention in the implementation of mining investment in North Sulawesi. By using a normative legal research method that is comprehensive both studies on aspects of the aspects of regulation and application in the field. With the use of this method, it is hoped that an appropriate formula will be found in addressing the continued occurrence of resistance in the form of community resistance to mining investment in North Sulawesi. Keywords: protection, community economic rights, resistance, mining